Apprehension toward generative artificial intelligence in healthcare: a multinational study among health sciences students - Sallam, Malik; Al-Mahzoum, Kholoud; Alaraji, Haya; Albayati, Noor; Alenzei, Shahad; AlFarhan, Fai; Alkandari, Aisha; Alkhaldi, Sarah; Alhaider, Noor; Al-Zubaidi, Dimah; Shammari, Fatma; Salahaldeen, Mohammad; et al. (Frontiers in Education, 2025)
BackgroundIn the recent generative artificial intelligence (genAI) era, health sciences students (HSSs) are expected to face challenges regarding their future roles in healthcare. This multinational cross-sectional study aimed to confirm the validity of the novel FAME scale examining themes of Fear, Anxiety, Mistrust, and Ethical issues about genAI. The study also explored the extent of apprehension among HSSs regarding genAI integration into their future careers.MethodsThe study was based on a self-administered online questionnaire distributed using convenience sampling. The survey instrument was based on the FAME scale, while the apprehension toward genAI was assessed through a modified scale based on State-Trait Anxiety Inventory (STAI). Exploratory and confirmatory factor analyses were used to confirm the construct validity of the FAME scale.ResultsThe final sample comprised 587 students mostly from Jordan (31.3%), Egypt (17.9%), Iraq (17.2%), Kuwait (14.7%), and Saudi Arabia (13.5%). Participants included students studying medicine (35.8%), pharmacy (34.2%), nursing (10.7%), dentistry (9.5%), medical laboratory (6.3%), and rehabilitation (3.4%). Factor analysis confirmed the validity and reliability of the FAME scale. Of the FAME scale constructs, Mistrust scored the highest, followed by Ethics. The participants showed a generally neutral apprehension toward genAI, with a mean score of 9.23 ± 3.60. In multivariate analysis, significant variations in genAI apprehension were observed based on previous ChatGPT use, faculty, and nationality, with pharmacy and medical laboratory students expressing the highest level of genAI apprehension, and Kuwaiti students the lowest. Previous use of ChatGPT was correlated with lower apprehension levels. Of the FAME constructs, higher agreement with the Fear, Anxiety, and Ethics constructs showed statistically significant associations with genAI apprehension.ConclusionThe study revealed notable apprehension about genAI among Arab HSSs, which highlights the need for educational curricula that blend technological proficiency with ethical awareness. Educational strategies tailored to discipline and culture are needed to ensure job security and competitiveness for students in an AI-driven future.